A method for preparing microwave absorbing coating
By deriving cotton fibers into biomass-derived tubular carbon fibers, and depositing MoS2 on its surface to form a composite structure, the problem of poor impedance matching of existing absorbing materials is solved, and efficient absorption of electromagnetic waves and excellent electromagnetic wave shielding performance are achieved.
Patent Information
- Application Number
- CN202411474071.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-01
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-12-01
AI Technical Summary
The existing absorbent materials are single in electromagnetic wave loss mechanism, poor impedance matching, and cannot meet the needs of practical applications.
By deriving cotton fibers from biomass-derived tubular carbon fibers and depositing MoS2 on its surface by hydrothermal method, a composite structure of MoS2 wrapped in tubular carbon fibers is formed, electromagnetic parameters are adjusted, and the polarization loss of heterogeneous interfaces is increased, thereby improving wave absorption performance.
It realizes efficient absorption of electromagnetic waves, has excellent electromagnetic wave shielding performance, is suitable for frequency range of 2~18 GHz, has a large effective absorption width, and is suitable for various equipment and products that require electromagnetic shielding.
Smart Images

Figure CN119108824B_ABST
Abstract
Description
[0001] This invention is a divisional application of patent application number 202311639848.4, and its invention name is "An electromagnetic shielding and absorbing material C / MoS2 and its preparation method and application". Technical Field
[0002] The invention relates to the technical field of electromagnetic shielding, and in particular to a method for preparing a radar absorbing coating. Background Art
[0003] Absorbing materials are a type of functional materials that can absorb electromagnetic waves in space. They can convert electromagnetic radiation into heat or other forms of energy, thereby reducing the reflection intensity of electromagnetic waves on the surface of the material. In engineering applications, in addition to requiring absorbing materials to have a high absorption rate of electromagnetic waves in a wider frequency band, they are also required to have properties such as light weight, temperature resistance, moisture resistance, and corrosion resistance. With the development of modern science and technology, at airports, flights are delayed due to electromagnetic interference; in hospitals, mobile phones often interfere with the normal operation of various electronic diagnostic and treatment instruments. In addition, the rapid development of radar detection technology has put forward higher technical requirements for the electromagnetic stealth performance of military equipment, and also put forward performance requirements for lightweight, high-strength and broadband for the absorbing materials used.
[0004] There are many types of carbon-based nano-absorbing materials, among which biomass-derived carbon materials can better retain the residual structure of natural raw materials after carbonization, such as special structural forms such as ordered pore structure, hollow tubular structure and hierarchical structure, which helps to improve the electromagnetic wave loss capacity of the material. Natural cotton fiber is a one-dimensional hollow tubular structure, which is composed of many concentric layers from the outside to the inside, with a nearly circular cross-sectional shape. Its material composition is simple and very suitable as a biomass-derived carbon source. However, pure cotton fiber-derived carbon has poor impedance matching and a single electromagnetic wave loss mechanism, which cannot meet the needs of practical applications. In order to optimize its absorbing performance, composite components can be introduced to design and regulate its microstructure. Nano molybdenum disulfide (MoS2) is a typical two-dimensional material that has a good response to electromagnetic waves, and has an ultra-thin thickness and ultra-large specific surface area. It can be used as an impedance matching regulator and composited with cotton fiber-derived carbon materials to achieve the purpose of improving impedance matching and improving absorbing performance. Summary of the invention
[0005] The purpose of the present invention is to provide an electromagnetic shielding and absorbing material C / MoS2.
[0006] Another object of the present invention is to provide a method for preparing the electromagnetic shielding and absorbing material C / MoS2, which solves the technical problems of agglomeration and uneven wrapping in the hydrothermal preparation of MoS2 and effectively improves the absorbing performance of the material.
[0007] The third object of the present invention is to provide an application of the above-mentioned electromagnetic shielding and absorbing material C / MoS2, specifically for preparing absorbing coatings.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] An electromagnetic shielding absorbing material, characterized in that: the absorbing material is a cotton fiber-derived C / MoS2 composite material, specifically, cotton fiber is used as a raw material to prepare biomass-derived tubular carbon fiber, and then MoS2 is hydrothermally deposited on the surface of the biomass-derived tubular carbon fiber to form a composite structure in which MoS2 wraps the tubular carbon fiber.
[0010] Furthermore, the preparation of biomass-derived tubular carbon fibers is to take absorbent cotton balls and perform heat treatment in an inert atmosphere at a heat treatment temperature of 600-800°C for a holding time of 5-6 h to obtain tubular carbon fibers having a cotton fiber structure.
[0011] Furthermore, the hydrothermal deposition of MoS2 is performed by dissolving sodium molybdate dihydrate (Na2MoO4∙2H2O) and thiourea (CH4N2S) in deionized water to form a mixed solution, then adding tubular carbon fibers for stirring and mixing, performing a hydrothermal reaction at 190~210°C for 20~24 hours, and then cooling to room temperature.
[0012] Furthermore, the dosage of sodium molybdate dihydrate, CH4N2S and deionized water in the mixed solution is 1-2 mmol:4-8 mmol:30 mL, and the dosage ratio of the tubular carbon fiber to the mixed solution is 1 mmol:3 mL.
[0013] Furthermore, after the hydrothermal reaction, the product was separated by centrifugation at 8000 r / min for 2 min, washed with deionized water and C2H6O for multiple times to remove impurities, and then dried in a drying oven at 60 °C for 24 h to obtain a cotton fiber-derived C / MoS2 composite material.
[0014] A preparation method of electromagnetic shielding and absorbing material C / MoS2, characterized in that: biomass-derived tubular carbon fibers are prepared using cotton yarn as raw material, MoS2 is hydrothermally deposited on the surface of the biomass-derived tubular carbon fibers to form a C / MoS2 composite structure in which MoS2 wraps the tubular carbon fibers, the preparation of the biomass-derived tubular carbon fibers is to take absorbent cotton balls, perform heat treatment under an inert atmosphere, the heat treatment temperature is 600-800°C, and the insulation time is 5-6 h to obtain tubular carbon fibers with a cotton fiber residual structure, the hydrothermal deposition of MoS2 is to dissolve sodium molybdate dihydrate (Na2MoO4∙2H2O) and thiourea (CH4N2S) in deionized water to form a mixed solution, then add the tubular carbon fibers to stir and mix, perform hydrothermal reaction at 190-210°C for 20-24 h, and then cool to room temperature, the amount of sodium molybdate dihydrate, CH4N2S and deionized water in the mixed solution is 1-2 mmol:4-8 mmol:30 mL, and the dosage ratio of the tubular carbon fiber to the mixed liquid is 1 mmol:3 mL.
[0015] During the preparation process, it was found that molybdenum disulfide easily agglomerates during the hydrothermal growth process, and the microwave absorption performance of the prepared composite material is not very ideal.
[0016] During the preparation process, the cotton fiber is first made into biomass-derived tubular carbon fiber and then added to the hydrothermal reaction system. The carbon fiber inherits the natural tubular structure of the raw material. Under the hydrothermal environment, it can form a steric hindrance effect in the solution, inhibiting the accumulation and agglomeration of MoS2 nanosheet layers, thereby increasing the specific surface area of the material and producing more active sites. At the same time, the carbon fiber also provides nucleation sites for the growth of MoS2 during the hydrothermal process, allowing MoS2 nanosheets to grow and cover the surface of the carbon fiber, forming a uniform and complete wrapping of the tubular carbon fiber.
[0017] Molybdenum disulfide synthesized by hydrothermal method on the surface of tubular carbon fiber derived from cotton fiber biomass has the characteristics of rich defects and many surface dangling bonds. The induced electrons in molybdenum disulfide move along the molecular network to form dissipative current, which has a good response to electromagnetic waves. The hollow tubular carbon fiber combined with the inside of molybdenum disulfide provides a longer transmission channel for the incident electromagnetic wave. The combination of the two can increase the multiple scattering and absorption of electromagnetic waves in the cavity. The one-dimensional tubular structure has a high specific surface area and high defect density, which can produce more space charge polarization and dipole polarization, accelerate the flow of electrons, and improve the conductivity loss of the material. The two components are obtained by in-situ growth and self-assembly to obtain C / MoS2 composite materials, which can improve the impedance matching characteristics of the composite material, adjust the electromagnetic parameters, increase the polarization loss of the heterogeneous interface, and thus improve the wave absorption performance of the composite material.
[0018] By adjusting the ratio of molybdenum atoms and carbon atoms during the hydrothermal process, the absorbing properties of the C / MoS2 composite material can be changed. Through continuous attempts, it was found that when the molar ratio of molybdenum and carbon atoms in the C / MoS2 composite material is adjusted to 1.5:10, a broadband and high-strength absorbing material can be obtained.
[0019] Furthermore, after the hydrothermal reaction, the product was separated by centrifugation at 8000 r / min for 2 min, washed with deionized water and C2H6O for multiple times to remove impurities, and then dried in a drying oven at 60 °C for 24 h to obtain a cotton fiber-derived C / MoS2 composite material.
[0020] The application of the electromagnetic shielding and absorbing material C / MoS2 prepared by the above method in the preparation of absorbing coatings.
[0021] An electromagnetic shielding absorbing coating, characterized in that it comprises a resin material, an absorbing material C / MoS2, a coupling agent, a dispersant, an anti-settling agent, a plasticizer and a solvent, wherein the absorbing material C / MoS2 is prepared from cotton fiber as a raw material into a biomass-derived tubular carbon fiber, and then MoS2 is hydrothermally deposited on the surface of the biomass-derived tubular carbon fiber to form a C / MoS2 composite structure in which MoS2 wraps the tubular carbon fiber.
[0022] Furthermore, the resin material is obtained by mixing epoxy resin and acrylic resin in a ratio of 1:1.
[0023] Furthermore, the coupling agent is a titanate coupling agent, the dispersant includes at least one of polyvinyl pyrrolidone, polyethylene glycol, polyvinyl alcohol and propylene carbonate, the anti-settling agent includes any one of bentonite, polyamide wax and polyethylene wax, the plasticizer includes at least one of dibutyl phthalate (DBP) and dioctyl phthalate (DOP), and the solvent can be at least one of ethanol, n-butanol, isopropanol, ethyl acetate, acetone or deionized water.
[0024] Further, according to the mass fraction, the amount of each component in the coating is as follows:
[0025] The resin material is 40~45 parts, C / MoS2 is 30~40 parts, the coupling agent is 2~4 parts, the dispersant is 1~2 parts, the dust suppressant is 0.5~1 parts, the plasticizer is 1~1.5 parts, and the solvent is 35~45 parts.
[0026] Further preferably, the amount of each component in the coating is 40 parts of resin material, 35 parts of C / MoS2, 3 parts of coupling agent, 1.5 parts of dispersant, 0.6 parts of dust suppressant, 1.2 parts of plasticizer, and 40 parts of solvent.
[0027] The method for preparing the electromagnetic shielding and absorbing coating is characterized by comprising the following steps:
[0028] (1) adding the absorbing material C / MoS2 and the coupling agent into a solvent for ultrasonic dispersion to obtain a mixed solution A, wherein the ultrasonic power is 800-1000 W and the ultrasonic time is 20-40 min;
[0029] (2) Adding resin material, plasticizer, dispersant and anti-settling agent to the mixed solution A and dispersing them under high-speed stirring, the stirring rate being 1500-2500 rpm and the stirring time being 1-1.5 h.
[0030] The present invention has the following technical effects:
[0031] The present invention uses cotton thread-derived carbon fiber to participate in the preparation of electromagnetic shielding and absorbing material C / MoS2, which can efficiently absorb electromagnetic waves to achieve the effect of shielding electromagnetic waves. It is prepared into an absorbing coating and tested to have a low reflection loss value of -41.7 dB in the frequency range of 2 to 18 GHz. In the thickness range of 1.0 to 5.0 mm, the effective absorbing width is large, and the effective absorbing width is 12.32 GHz, specifically 5.68 to 18 GHz. The material has excellent electromagnetic wave shielding performance. The coating can be applied to various equipment and products that require electromagnetic shielding in life and work, such as shale gas mining equipment, mining machinery and equipment, medical instruments, communication equipment, and aerospace equipment, so as to reduce the interference of electromagnetic waves on the normal operation of various equipment. In addition, it can be used in military equipment to achieve shielding function by absorbing electromagnetic waves. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 : Scanning electron microscope image of biomass-derived C / MoS2 prepared in Example 1.
[0033] Figure 2 : Scanning electron microscope image of C / MoS2 prepared in Comparative Example 1.
[0034] Figure 3 : Reflectivity graph of biomass-derived C / MoS2 prepared in Example 1.
[0035] Figure 4 : Reflectivity diagram of C / MoS2 prepared in Comparative Example 1.
[0036] Figure 5 : Reflectivity graph of biomass-derived C / MoS2 prepared in Example 2.
[0037] Figure 6 : Reflectivity graph of biomass-derived C / MoS2 prepared in Example 3. DETAILED DESCRIPTION
[0038] The present invention is described in detail below through examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the above-mentioned contents of the present invention.
[0039] Example 1
[0040] A method for preparing an electromagnetic shielding and absorbing material C / MoS2 comprises the following steps:
[0041] (1) Take an absorbent cotton ball, dry it in a vacuum environment, and then heat treat it in an inert atmosphere at a temperature of 700 °C for a holding time of 5.5 h to obtain a tubular carbon fiber with a cotton fiber structure;
[0042] (2) Sodium molybdate dihydrate (Na2MoO4∙2H2O) and thiourea (CH4N2S) are dissolved in deionized water to form a mixed solution, and then tubular carbon fibers are added and stirred and mixed, and a hydrothermal reaction is carried out at 200°C for 24 h, and then cooled to room temperature, wherein the amount of sodium molybdate dihydrate, thiourea and deionized water in the mixed solution is 1.5 mmol:6 mmol:30 mL, and the amount ratio of the tubular carbon fibers to the mixed solution is 1 mmol:3 mL;
[0043] (3) After the thermal reaction, the product obtained by the hydrothermal reaction was separated by centrifugation at 8000 r / min for 2 min. The product was washed with deionized water and C2H6O for multiple times to remove impurities and then dried in a drying oven at 60 °C for 24 h to obtain a cotton fiber-derived C / MoS2 composite material with a molar ratio of molybdenum to carbon atoms of 1.5:10.
[0044] from Figure 1 It can be seen that the biomass-derived carbon generated by carbonizing the cotton fibers first retains the fiber structure very well, and MoS2 nanosheets grow in situ on the surface of the carbon fibers. MoS2 is evenly distributed on the surface of the carbon fibers and self-assembles to form a C / MoS2 composite material, which improves the impedance matching characteristics of the composite material, adjusts the electromagnetic parameters, and increases the polarization loss of the heterogeneous interface, thereby improving the wave absorption performance of the composite material.
[0045] The prepared C / MoS2 composite material was mixed with paraffin, and its electromagnetic properties were tested by the coaxial method. Specifically, the sample to be tested was mixed with paraffin according to a certain filling ratio, and then placed in a coaxial mold and pressed into a coaxial ring with an inner diameter of about 3 mm, an outer diameter of about 7 mm, and a thickness of about 2 mm. The coaxial ring was placed in a coaxial line fixture and connected to the two coaxial lines ports of a vector network analyzer through a connector. The excitation signal emitted by the signal source of the network vector analyzer was divided into two signals by a signal separator. One signal entered the receiver test as a reference signal, and the other signal was extracted by a directional coupler. Finally, the amplitude and phase of the two signals were obtained by the processing display unit, and the scattering parameters and of the absorbing material in the frequency range of 2.0~18.0 GHz were obtained. The transmission coefficient and reflection coefficient were obtained from the scattering parameters, and then the electromagnetic parameters of the absorbing material were determined. After obtaining the dielectric constant and magnetic permeability, the reflectivity values of the sample at different frequencies under different thicknesses were calculated according to the relevant formulas. The results are shown in Figure 3 As shown in the figure, when the coating thickness is 4.5 mm, the minimum reflection loss value of C / MoS2 is -41.7 dB. In the thickness range of 1.0~5.0 mm, the effective absorption width is 12.32 GHz, which can achieve more than 95% effective absorption of electromagnetic waves in the range of 5.68-18 GHz.
[0046] Comparative Example 1
[0047] A method for preparing C / MoS2 comprises the following steps:
[0048] (1) Sodium molybdate dihydrate (Na2MoO4∙2H2O) and thiourea (CH4N2S) are dissolved in deionized water to form a mixed solution, and then absorbent cotton balls are combed into fibers and added into the mixed solution for stirring and mixing, and a hydrothermal reaction is carried out at 200°C for 24 hours, and then cooled to room temperature. The amount of sodium molybdate dihydrate, thiourea and deionized water in the mixed solution is 1.5 mmol:6 mmol:30 mL;
[0049] (2) After the hydrothermal reaction, the product was separated by centrifugation at 8000 r / min for 2 min, and then washed with deionized water and C2H6O several times to remove impurities and dried in a drying oven at 60 °C for 24 h to obtain a C / MoS2 precursor;
[0050] (3) The C / MoS2 precursor was placed in an inert atmosphere for heat treatment at a temperature of 700 °C and a holding time of 5.5 h to obtain C / MoS2.
[0051] In Comparative Example 1, MoS2 is first generated on the surface of cotton fiber, and then further carbonized. The biggest problem in the preparation process is that it is impossible to improve the wave absorption performance of C / MoS2 material by adjusting the ratio of molybdenum / carbon atoms. In the hydrothermal process, cotton fiber that has not been carbonized cannot provide more attachment points for MoS2 nucleation and growth. Therefore, the coating effect of MoS2 on the fiber surface is poor, and more heterogeneous structures cannot be formed in the C / MoS2 composite material. At the same time, due to the lack of steric effect, MoS2 undergoes obvious agglomeration, such as Figure 2 As shown, this has an adverse effect on the absorbing performance. Figure 4 It can be seen that the minimum reflection loss value of C / MoS2 prepared in Comparative Example 1 is -12.5 dB, and within the thickness range of 1.0~5.0 mm, the effective absorption width is 10.5 GHz.
[0052] During the preparation process, we also tried to directly use other tubular carbon fiber materials (non-cotton fiber biomass-derived carbon fibers) to prepare C / MoS2 composites, but the performance of the prepared composites was not as good as that of the C / MoS2 composites prepared with cotton fiber as raw material.
[0053] Example 2
[0054] A method for preparing an electromagnetic shielding and absorbing material C / MoS2 comprises the following steps:
[0055] (1) Take an absorbent cotton ball, dry it in a vacuum environment, and then heat treat it in an inert atmosphere at a temperature of 800 °C for 5 h to obtain a tubular carbon fiber with a cotton fiber structure.
[0056] (2) Sodium molybdate dihydrate (Na2MoO4∙2H2O) and thiourea (CH4N2S) are dissolved in deionized water to form a mixed solution, and then tubular carbon fibers are added and stirred and mixed, and a hydrothermal reaction is carried out at 190 °C for 22 h, and then cooled to room temperature, wherein the amount of sodium molybdate dihydrate, CH4N2S and deionized water in the mixed solution is 1 mmol:4 mmol:30 mL, and the amount ratio of the tubular carbon fiber to the mixed solution is 1 mmol:3 mL;
[0057] (3) After the thermal reaction, the product obtained by the hydrothermal reaction was separated by centrifugation at 8000 r / min for 2 min. The product was washed with deionized water and C2H6O for multiple times to remove impurities and then dried in a drying oven at 60 °C for 24 h to obtain a cotton fiber-derived C / MoS2 composite material with a molar ratio of molybdenum to carbon atoms of 1:10.
[0058] like Figure 5As shown in the figure, when the coating thickness is 5 mm, the minimum reflection loss value of C / MoS2 is -33.6 dB. In the thickness range of 1.0~5.0 mm, the effective absorption width is 12.3 GHz, which can achieve 95% effective absorption of electromagnetic waves in the range of 5-18 GHz.
[0059] Example 3
[0060] A method for preparing an electromagnetic shielding and absorbing material C / MoS2 comprises the following steps:
[0061] (1) Take an absorbent cotton ball, dry it in a vacuum environment, and then heat treat it in an inert atmosphere at a temperature of 600 °C for 6 h to obtain a tubular carbon fiber with a cotton fiber structure.
[0062] (2) Sodium molybdate dihydrate (Na2MoO4∙2H2O) and thiourea (CH4N2S) are dissolved in deionized water to form a mixed solution, and then tubular carbon fibers are added and stirred and mixed, and a hydrothermal reaction is carried out at 210 °C for 20 h, and then cooled to room temperature, wherein the amount of sodium molybdate dihydrate, CH4N2S and deionized water in the mixed solution is 2 mmol:8 mmol:30 mL, and the amount ratio of the tubular carbon fiber to the mixed solution is 1 mmol:3 mL;
[0063] (3) After the thermal reaction, the product obtained by the hydrothermal reaction was separated by centrifugation at 8000 r / min for 2 min. The product was washed with deionized water and C2H6O for multiple times to remove impurities and then dried in a drying oven at 60 °C for 24 h to obtain a cotton fiber-derived C / MoS2 composite material with a molar ratio of molybdenum to carbon of 1:5.
[0064] The results are as follows Figure 3 As shown in the figure, when the coating thickness is 4.5 mm, the minimum reflection loss value of C / MoS2 is -41.7 dB, and in the thickness range of 1.0~5.0 mm, the effective absorption width is 12.32 GHz.
[0065] like Figure 6 As shown in the figure, when the coating thickness is 5 mm, the minimum reflection loss value of C / MoS2 is -28.6 dB. In the thickness range of 1.0~5.0 mm, the effective absorption width is 12.7 GHz, which can achieve 95% effective absorption of electromagnetic waves in the range of 5-18 GHz.
[0066] Example 4
[0067] The magnetic shielding absorbing material C / MoS2 prepared in Example 1 is used to prepare an absorbing coating, and the preparation method thereof comprises the following steps:
[0068] (1) The absorbing material C / MoS2 and the coupling agent prepared in Example 1 were added to a solvent for ultrasonic dispersion to obtain a mixed solution A. The ultrasonic power was 1000 W and the ultrasonic time was 30 min.
[0069] (2) Adding resin material, plasticizer, dispersant and anti-settling agent to the mixed solution A and dispersing them under high-speed stirring, the stirring rate is 1500 rpm, and the stirring time is 1.5 h;
[0070] The amount of each component in the coating is 40 parts of resin material, 35 parts of C / MoS2, 3 parts of coupling agent, 1.5 parts of dispersant, 0.6 parts of dust suppressant, 1.2 parts of plasticizer, and 40 parts of solvent, wherein the resin material is a mixture of epoxy resin and acrylic resin in a 1:1 ratio, the coupling agent is a titanate coupling agent, the dispersant is polyvinyl pyrrolidone, the anti-settling agent is polyethylene wax, the plasticizer is dibutyl phthalate (DBP), and the solvent is ethanol and isopropanol mixed in a volume ratio of 1:1.
[0071] Example 5
[0072] The magnetic shielding absorbing material C / MoS2 prepared in Example 2 is used to prepare an absorbing coating, and the preparation method thereof comprises the following steps:
[0073] (1) The absorbing material C / MoS2 and the coupling agent prepared in Example 2 are added to a solvent for ultrasonic dispersion to obtain a mixed solution A. The ultrasonic power is 900 W and the ultrasonic time is 20 min.
[0074] (2) Adding resin material, plasticizer, dispersant and anti-settling agent to the mixed solution A and dispersing them under high-speed stirring, the stirring rate is 2500 rpm, and the stirring time is 1 h;
[0075] The resin material is a mixture of epoxy resin and acrylic resin in a ratio of 1:1, the coupling agent is a titanate coupling agent, the dispersant is polyethylene glycol, the anti-settling agent is bentonite, the plasticizer is dioctyl phthalate (DOP), and the solvent is ionized water. Calculated by weight, the amount of each component in the coating is 45 parts of resin material, 40 parts of C / MoS2, 4 parts of coupling agent, 2 parts of dispersant, 1 part of dust suppressant, 1.5 parts of plasticizer, and 45 parts of solvent.
[0076] Example 6
[0077] The magnetic shielding absorbing material C / MoS2 prepared in Example 2 is used to prepare an absorbing coating, and the preparation method thereof comprises the following steps:
[0078] (1) The absorbing material C / MoS2 and the coupling agent prepared in Example 3 were added to a solvent and ultrasonically dispersed to obtain a mixed solution A. The ultrasonic power was 800 W and the ultrasonic time was 40 min.
[0079] (2) Adding resin material, plasticizer, dispersant and anti-settling agent to the mixed solution A and dispersing them under high-speed stirring. The stirring rate is 1800 rpm and the stirring time is 1 h.
[0080] The resin material is a mixture of epoxy resin and acrylic resin in a ratio of 1:1, the coupling agent is a titanate coupling agent, the dispersant is polyvinyl alcohol, the anti-settling agent is polyethylene wax, the plasticizer is dibutyl phthalate (DBP), and the solvent is ethyl acetate; the amount of each component in the coating is as follows, calculated by mass:
[0081] The resin material is 42 parts, C / MoS2 is 30 parts, the coupling agent is 2 parts, the dispersant is 1 part, the dust suppressant is 0.5 parts, the plasticizer is 1 part, and the solvent is 35 parts.
[0082] The performance of the absorbing coatings prepared in Examples 4-6 was tested. The absorbing performance of the absorbing coating fabric was tested in a microwave darkroom using a vector network analyzer using a reflectivity bow measurement method. The test angle was 15° and the test range was 2 to 18 GHz. The test was performed in accordance with GJB2038-1994 "Test Method for Reflectivity of Radar Absorbing Materials". The results are shown in Table 1.
[0083] Table 1:
[0084]
[0085] It can be seen that after the cotton fiber biomass-derived C / MoS2 prepared by the present invention is prepared into a coating, its wave absorbing performance is maintained at a high level.
Claims
1. A C / MoS2-based microwave absorbing coating, characterized in that: The invention comprises a resin material, an absorbing material C / MoS2, a coupling agent, a dispersant, an anti-settling agent, a plasticizer and a solvent. The absorbing material C / MoS2 is prepared from cotton fiber as a raw material into a biomass-derived tubular carbon fiber, and then MoS2 is hydrothermally deposited on the surface of the biomass-derived tubular carbon fiber to form a C / MoS2 composite structure in which MoS2 wraps the tubular carbon fiber. The preparation of the biomass-derived tubular carbon fiber is to take an absorbent cotton ball, perform a heat treatment in an inert atmosphere, the heat treatment temperature is 600-800°C, and the insulation time is 5-6 h to obtain a tubular carbon fiber with a cotton fiber residual structure. The hydrothermally deposited MoS2 is to dissolve sodium molybdate dihydrate (Na2MoO4∙2H2O) and thiourea (CH4N2S) in deionized water to form a mixed solution, and then the tubular carbon fiber is added for stirring and mixing, and a hydrothermal reaction is performed at 190-210°C for 20-24 h, and then cooled to room temperature, the dosage of sodium molybdate dihydrate, CH4N2S and deionized water in the mixed solution is 1~2 mmol:4~8 mmol:30mL, and the dosage ratio of the tubular carbon fiber to the mixed solution is 1 mmol:3 mL.
2. A radar absorbing coating as claimed in claim 1, characterized in that: The resin material is obtained by mixing epoxy resin and acrylic resin in a ratio of 1:
1.
3. The radar absorbing coating according to claim 1 or 2, characterized in that: The coupling agent is a titanate coupling agent, the dispersant includes at least one of polyvinyl pyrrolidone, polyethylene glycol, polyvinyl alcohol and propylene carbonate, the anti-settling agent includes any one of bentonite, polyamide wax and polyethylene wax, the plasticizer includes at least one of dibutyl phthalate (DBP) and dioctyl phthalate (DOP), and the solvent is at least one of ethanol, n-butanol, isopropanol, ethyl acetate, acetone or deionized water.
4. The radar absorbing coating according to claim 1 or 2, characterized in that: Calculated by mass, the amount of each component in the coating is as follows: 40~45 parts of resin material, 30~40 parts of C / MoS2, 2~4 parts of coupling agent, 1~2 parts of dispersant, 0.5~1 parts of dust suppressant, 1~1.5 parts of plasticizer, and 35~45 parts of solvent.
5. A method for preparing a C / MoS2-based radar absorbing coating as claimed in claim 1, characterized in that: The steps include: (1) adding the absorbing material C / MoS2 and the coupling agent to a solvent for ultrasonic dispersion to obtain a mixed solution A, wherein the ultrasonic power is 800-1000 W and the ultrasonic time is 20-40 min, and the solvent is at least one of ethanol, n-butanol, isopropanol, ethyl acetate, acetone or deionized water; (2) Add resin material, plasticizer, dispersant and anti-settling agent to mixed liquid A and disperse them under high-speed stirring at a rate of 1500-2500 rpm for 1-1.5 h.
6. A method for preparing the radar absorbing coating according to claim 5, characterized in that: The resin material is obtained by mixing epoxy resin and acrylic resin in a ratio of 1:
1.
7. The method for preparing the radar absorbing coating according to claim 5 or 6, characterized in that: The coupling agent is a titanate coupling agent, the dispersant includes at least one of polyvinyl pyrrolidone, polyethylene glycol, polyvinyl alcohol and propylene carbonate, the anti-settling agent includes any one of bentonite, polyamide wax and polyethylene wax, the plasticizer includes at least one of dibutyl phthalate (DBP) and dioctyl phthalate (DOP), and the solvent is at least one of ethanol, n-butanol, isopropanol, ethyl acetate, acetone or deionized water.
8. The method for preparing the radar absorbing coating according to claim 7, characterized in that: Calculated by mass, the amount of each component in the coating is as follows: 40~45 parts of resin material, 30~40 parts of C / MoS2, 2~4 parts of coupling agent, 1~2 parts of dispersant, 0.5~1 parts of dust suppressant, 1~1.5 parts of plasticizer, and 35~45 parts of solvent.
Citation Information
Patent Citations
Molybdenum disulfide combined nitrogen porous carbon material as well as preparation method and application thereof
CN112063365A
Biomass-based FeS particle composite fiber, preparation method thereof and electromagnetic absorption material
CN116084158A
Electromagnetic shielding wave-absorbing material C / MoS2 as well as preparation method and application thereof
CN117691367A